What are the essential cognitive requirements for prospection (thinking about the future)? - Osman, Magda (Frontiers in Psychology, 2014)
Placing the future centre stage as a way of understanding cognition is gaining attention in psychology. The general modern label for this is “prospection” which refers to the process of representing and thinking about possible future states of the world. Several theorists have claimed that episodic and prospective memory, as well as hypothetical thinking (mental simulation) and conditional reasoning are necessary cognitive faculties that enable prospection. Given the limitations in current empirical efforts connecting these faculties to prospection, the aim of this mini review is to argue that the findings show that they are sufficient, but not necessary for prospection. As a result, the short concluding section gives an outline of an alternative conceptualisation of prospection. The proposal is that the critical characteristics of prospection are the discovery of, and maintenance of goals via causal learning.